Leadership for the 21st century : our labors today will shape our country's future - Ramos, Fidel V., 1928- ([Manila, Philippines] : Friends of Steady Eddie, 1997)
The need for a fit between the leader and the time is a recurring motif in history. Leaders for all seasons are all too rare. Churchill was perhaps the greatest of wartime leaders yet once peace was restored.
1. The Quality of government -- 2. Faith in the Filipino future -- 3. A vision of community -- 4. Vanguards of modernization -- 5. Building the structure of security -- 6. The laughter of our people -- 7. The past is present -- 8. Faster, higher stronger
Includes index.
Keywords: PHILIPPINES -- POLITICS AND GOVERNMENT